Organizational context, system context and cognitive styles as determinants of user satisfaction / Norol Hamiza Zamzuri ... [et al.] - Zamzuri, Norol Hamiza; Kassim, Erne Suzila; Mohd Nasir, Hazira; Shahrom, Melissa (2010)
E-learning has been a wide research discussion and the evaluation of e-learning interface design has been an imperative importance discussion among previous researchers. But lack of studies reveal the influence of cognitive styles with system characteristics and information success which lead to user satisfaction. Despite considerable empirical research, results on the relationships among constructs related to information system (IS) satisfaction and process value, as well as the determinants of IS satisfaction, are often inconsistent. A comprehensive understanding of IS satisfaction thus remains elusive. In an attempt to address this situation, we present and test a comprehensive theoretical model that explains interrelationships among different constructs representing the organizational and system context and usage which lead to satisfaction. This study will also identify the usage of differences between two types of cognitive styles which are adaptors and innovators. Using a survey, we attempt to investigate the factors that motivate academics to use e-learning system and to examine whether there is a significant difference in the use of the e learning system between different cognitive styles. Findings of the study suggest top management emphasis, facilitating conditions and system quality are the factors that motivate academics to use the system. In addition, there is also a different in use among innovators and adaptors. Based on the findings, implication for future research is offered.